UJI SENSITIVITAS TES MONOFILAMEN UNTUK DETEKSI DINI NEUROPATI KUSTA SUBKLINIS PADA KONTAK ERAT PASIEN KUSTA TIPE MULTIBASILAR - Halida Novita,* Nani Kurniani,* Andi Basuki Prima Birawa* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION LEPROSY IS INFECTIOUS DISEASE AFFECTING SKIN AND NERVE BECAUSE HOUSEHOLD CONTACT IS STRONG RISK FACTOR OF SUBLINICAL LEPROSY IT IS IMPORTANT TO CONDUCT EARLY DETECTION TO PREVENT CLINICAL LEPROSY SEMMESWEINTEIN MONOFILAMENT HAS A GOOD RELIABILITY TO EXAMINE A SENSORY FUNCTION OF PERIPHERAL NERVE SUBCLINICAL LEPROSY NEUROPATHY IS A SILENT NEUROPATHY THAT CAN BE DETECTED FROM AN EXAMINATION ALTHOUGH THERE ARE NO SUBJECTIVE COMPLAINTS PGL1 IS A SPECIFIC ANTIGEN TO M LEPRAE AND INCREASING OF IGM PGL1 LEVEL IS AN INDICATOR OF M LEPRAE INFECTION